Foreword - Byrne, Iain (Victoria University of Wellington Law Review, 2009)
For over 25 years, the International Centre for the Legal Protection of Human Rights has been committed to advancing human rights through international and regional mechanisms. However, the majority of the world’s population has no access to such systems. The result is a denial of justice and impunity for offending states. The challenge is how to convert desire for change into a practical agenda for action. This foreword introduces the collection of articles that tackle this very issue.